Primary cutaneous apocrine carcinoma: Case report and literature review - Seema Chadha; Rakesh Kumar; Sanjeev Singhal; Shilpa Ruhela (Wolters Kluwer Medknow Publications, 2021)
Primary cutaneous apocrine carcinomas are rare cutaneous adnexal neoplasm with less than 100 cases reported in the literature. The tumor arises in areas rich in apocrine glands particularly axilla, modified apocrine glands such as ceromucinous and Moll's glands. Most of these carcinomas are indolent and slowly growing but few rapidly progressive and extremely aggressive? cases have also been reported. Wide local excision with clear margins and sentinel lymph node biopsy is standard treatment of choice.This case was of much interest from the diagnostic point of view both microscopically as well as immunohistochemically. We report a case of 46-year-old man who presented to our hospital with an ulcerated painless nodular mass in his right axilla.With combined use of microscpic features, special stains and immunohistochemical examination the case was correctly diagnosed as primary cutaneous apocrine carcinoma.